The development of thermal lattice Boltzmann models in incompressible limit - Che Sidik, Nor Azwadi (Journal of Fundamental Sciences, 2007)
In this paper, an incompressible two-dimensional (2-D) and three-dimensional (3-D) thermohydrodynamics for the lattice Boltzmann scheme are developed. The basic idea is to solve the velocity field and the temperature field using two different distribution functions. A derivation of the lattice Boltzmann scheme from the continuous Boltzmann equation for 2-D is discussed in detail. By using the same procedure as in the derivation of the discretised density distribution function, we found that new lattice of four-velocity (2-D) and eight-velocity(3-D) models for internal energy density distribution function can be developed where the viscous and compressive heating effects are negligible. These models are validated by the numerical simulation of the 2-D porous plate Couette flow problem where the analytical solution exists and the natural convection flows in a cubic cavity.